Мотивація як суб’єктивний чинник протидії правовому нігілізму в діяльності поліції - Дякова, О. О.; Diakova, O. O. (Форум права. - 2017. - № 5. - С. 132–137, 2017)
Досліджено та обґрунтовано зв’язок мотивуючих факторів, що чинять вплив на працівників Національної поліції України у процесі їх правозастосовної діяльності. Метою статті є дослідження природи та змісту мотивів, які впливають на поліцейських і забезпечують підвищення рівня їх правової свідомості. Аналіз змісту поняття мотивації та її впливу на підвищення рівня правосвідомості поліцейських здійснено з використанням юридикологічного методу. Досліджено вплив на мотиваційну сферу поліцейського присяги, моральних і матеріальних заохочень та зацікавленість в реалізації можливості кар’єрного зростання.

The connection of motivating factors which influence the employees of the National Police of Ukraine in the process of their law enforcement activity was investigated and justified. The aim of the work was to study the nature and content of motives that affect policemen and provide an increase in the level of their legal consciousness. Analysis of the motivation content and its effect on increasing level of legal police was executed using the method of analysis and comparison with the practical police activities. It is proved that the motive is what motivates a person to make or refuse to perform certain acts, it encourages people to act the way they do. It was determined that motivation for the lawful conduct of police officers should be ensured mainly through a motivational component in the process of legal education. The possibility of influence on the motivational sphere of police oaths of a policeman, the words of which should be the main ideological and motivating content of the policeman’s activity in the future, is explored. It was noted that the process affects the motivation of police activity leaders, so to speak employers. This is an effective mechanism in their hands, which can lead to great success, or vice versa, until the decline. It was proved that the main motive of effective, efficient and legitimate police activities are legitimate financial interest in the behavior and interest in the implementation of career opportunities. The correlation between the concepts of «motive» and «motivation» was established, which was defined as a factor and process of influence of this factor on the object – the consciousness of the policeman. The acquired result can be used in further scientific developments of the problem of overcoming nihilism in law enforcement activities of policemen, in the practice of police psychologists and police officers at all levels for the effective organization of the activities of subordinates, in the process of organizing vocational training of police officers.

Исследована и обоснована связь мотивирующих факторов, оказывающих воздействие на работников Национальной полиции Украины в процессе их правоприменительной деятельности. Целью работы является исследование природы и содержания мотивов, влияющих на полицейских и обеспечивающих повышение уровня их правового сознания. Анализ содержания понятия мотивации и ее влияния на повышение уровня правосознания полицейских осуществлено с использованием метода анализа и сопоставления с практической деятельностью полиции. Исследовано влияние на мотивационную сферу полицейского присяги, материальных поощрений и заинтересованности в реализации возможности карьерного роста.
Motivation as a Subjective Factor in Counteracting Legal Nihilism in Police Activity
Мотивация как субъективный фактор противодействия правовому нигилизму в деятельности полиции
Дьякова О. О. Мотивація як суб’єктивний чинник протидії правовому нігілізму в діяльності поліції [Електронний ресурс] / О. О. Дьякова // Форум права. - 2017. - № 5. - С. 132–137. – Режим доступу: http://nbuv.gov.ua/j-pdf/FP_index.htm_2017_5_20.pdf.
Дьякова О. О. Мотивація як суб’єктивний чинник протидії правовому нігілізму в діяльності поліції. Форум права: електрон. наук. фахове вид. 2017. № 5. С. 132–138. URL: http://nbuv.gov.ua/j-pdf/FP_index.htm_2017_5_20.pdf.
Дьякова О. О. "Мотивація як суб’єктивний чинник протидії правовому нігілізму в діяльності поліції." Форум права 5 (2017): 132–137.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Держава і право. State and Law. Государство и право; поліція; полиция; police; правовий нігілізм; поліцейський; мотив; мотивація правомірної поведінки особи; присяга; протидія правовому нігілізму; мотиви правомірної поведінки; правомірна поведінка; правовой нигилизм; полицейский; мотивация; противодействие правовому нигилизму; legal nihilism; police officers; motive; motivation of lawful behavior; oath; antagonism to legal nihilism